Fiqh Contestation on Women's Public Leadership in Indonesia and Malaysia: Reproducing Qur'anic and Hadith Interpretations - Muqtada, Muhammad Rikza; Istianah; Ahmad Sharifuddin bin Mustapha; Mufid, Abdul (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2024)
This paper discusses the contestation of women's public leadership discourse among feminist activists in Indonesia and Malaysia and how the reproduction of fiqh on women's public leadership in both countries takes place. This research is a field study with data collection through interviews and direct interaction with women activists in both countries and documenting their works. Using the Islamic activism approach, it was found that: 1) The issue of women leaders in Indonesia and Malaysia is complex. Women are often held back by culture, religion and politics. Muslim feminist groups face resistance from conservative groups when they try to challenge gender inequality. Furthermore, some sharia law make it harder for women to get legal protection and justice. More legal rights and support for women are therefore required to make politics more equal. 2) Feminist activists in Indonesia and Malaysia have reinterpreted Islamic texts to promote gender equality. They offer gender-responsive interpretation of the Qur'an and Hadith deemed to be fairer while supporting support social justice and gender equality. 3) The fiqh product of leadership concludes that the moral ideal in the Qur'an and hadith is for leaders to be competent (qawwām). People who fit this profile are well-suited to lead, particularly in a country that adheres to democratic principles.